STRATEGI MANAJEMEN KEUANGAN SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI MA YAMISA SOREANG - Barlian, Ujang Cepi; Permana, Rudiansah Sidik; Mahmudah, Rivatul (Komunitas Manajemen Kompetitif, 2022)
Improving the quality of education is influenced by aspects of financial management. Schools must have clear financial management planning, implementation, supervision and responsibility. The existence of MA Yamisa, which was founded in 1981 until now, is one of the reasons for its successful financial management. With descriptive qualitative research methods, this study is intended to determine the school's financial management strategy in improving the quality of education at MA Yamisa Soreang. The research data collection instrument used interviews, observation, and documentation. Checking the validity of the data using triangulation of data sources and triangulation of methods. The results showed that MA Yamisa's financial management strategy was to carry out financial planning by holding coordination meetings to formulate programs, sources of funds, and budgets for one year, implement budgets according to plans, evaluate and make financial accountability reports.